Synthesis, spectroscopic characterization and antimicrobial activity studies of 2-Butyl-4-chloro-5-formylimidazole thiosemicarbazone and its manganese (II) complex - A. Sreenath Reddy, M. Sivasankar Reddy, Venkata Subbaiah kotakadi, P.V. Chalapathi, A. Varada Reddy (Journal of Applied Pharmaceutical Science, 2014)
A novel chelating tridentate organic ligand, 2-Butyl-4-chloro-5-formylimidazole thiosemicarbazone(L) is synthesized and characterized by using spectroscopic techniques like elemental analysis, FT-IR, 1H and 13C NMR, UV-vis and Mass spectrometry. The free ligand is then used for the synthesis of Mn(II) complex thoroughly characterized by FT-IR, EPR and electronic spectral analysis. The complex is found to have characteristic d5 electronic spectrum and the geometry of the complex is identified as octahedron based on the g value obtained from the EPR spectrum. Both the ligand and Mn(II)L2 compounds are found to exhibit similar antimicrobial activity against the gram –ve and gram +ve bacteria.
Keywords: Thiosemicarbazones,Manganese(II) complex, EPR spectra, Antimicrobial activity.